"Evil Disposed Netherlanders": The Dutch West India Company's Opposition to Danish Activity on the Gold Coast, 1657–1662. Issue 3 (31st December 2018) - Svensli, Fredrik Hyrum
Abstract : The aim of this article is to analyse the on-the-spot interaction between agents of the Dutch West India Company and Danish African Company and African rulers on the Gold Coast from 1657 to 1662. The region saw a surge in European activity and rivalry in this period. The Scandinavian trading companies have received less scholarly attention compared to the Dutch and the English. The Danish African Company was an undercover Dutch enterprise, and has traditionally been studied from a purely Dutch or Danish standpoint. However, by combining Dutch and Danish sources and focusing on Dutch opposition to "Danish" activity on the Gold Coast, which incorporated local rulers, the author has challenged nationalistic and Eurocentric approaches in the historiography. Moreover, by concentrating on the forgotten but nonetheless strategically important site of Akong, the author identifies how local dynamics influenced the evolution of the Dutch and Danish maritime empires.